2021
DOI: 10.1111/1365-2435.13810
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evolution ameliorates the long‐term plastic effects of warming, temperature fluctuations and heat waves on predator–prey interaction strength

Abstract: How thermal evolution may affect trophic interactions and its implications for trophic system stability remains unstudied. To advance insights in how global warming shapes trophic interactions, we need to consider besides increases in mean temperatures, also daily thermal fluctuations (DTF) and heat waves (HW), and how their effects are modulated by thermal evolution. Using a common‐garden approach, we tested how each thermal factor affected predator metabolic rate and functional response parameters, and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 80 publications
4
29
1
Order By: Relevance
“…Previous studies showed that warming may increase predatorprey system stability (Rall et al, 2010;Sentis et al, 2015;Wang et al, 2021). Our current experiment extends these studies by (a)…”
Section: Effects Of Warming and Turbidity On System Stabilitysupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies showed that warming may increase predatorprey system stability (Rall et al, 2010;Sentis et al, 2015;Wang et al, 2021). Our current experiment extends these studies by (a)…”
Section: Effects Of Warming and Turbidity On System Stabilitysupporting
confidence: 84%
“…To assess effects on the short‐term predation rate and long‐term system stability, we conducted a functional response experiment and an experiment to quantify the prey’s population dynamics for each of the 16 treatment combinations. We then estimated functional response parameters (search rates and handling times) and carrying capacity, and used these estimated parameters together with prey body mass and predator metabolic rates at 20 and 24°C that were quantified in a previous study (Wang et al, 2021) to parametrize population dynamic models and predict system stability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While our study provides some insights into how changes in mean temperature and temperature variation affect diversity, the nature of the system and the length of the experiment mean several important processes are not accounted for. Among these, the design of our study does not account for how evolutionary changes in species may counteract or exacerbate the effects of changing temperature regime (Hoffmann & Sgró, 2011 ; Wang et al, 2021 ). Previous experiments have also demonstrated how global change‐mediated changes to trophic interactions can lead to altered diversity (Hammill, Johnson, et al, 2018 ), and how combined global changes can lead to reduced diversity (Atwood et al, 2015 ; Kratina et al, 2012 ; Tabi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the topic (Colinet et al, 2015) found that insects subjected to fluctuating temperatures within their nonlethal thermal ranges elicit diverse responses. However, empirical studies of the effects of fluctuating temperatures on odonates remain rare (Frances et al, 2017; Verheyen & Stoks, 2019; Wang et al, 2021). We conducted two complementary experiments to address how warming and body size differentials during larval development influence emergence timing, body size, wing morphology and adult assemblage composition in three species of dragonfly.…”
Section: Introductionmentioning
confidence: 99%